2023
DOI: 10.3390/nu15081811
|View full text |Cite
|
Sign up to set email alerts
|

The Beneficial Effects of Soybean Proteins and Peptides on Chronic Diseases

Abstract: With lifestyle changes, chronic diseases have become a public health problem worldwide, causing a huge burden on the global economy. Risk factors associated with chronic diseases mainly include abdominal obesity, insulin resistance, hypertension, dyslipidemia, elevated triglycerides, cancer, and other characteristics. Plant-sourced proteins have received more and more attention in the treatment and prevention of chronic diseases in recent years. Soybean is a low-cost, high-quality protein resource that contain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 115 publications
0
4
0
Order By: Relevance
“…The protein extraction from peas, chickpeas, and other beans has attracted attention due to its good amino acid balance and high protein bioavailability (Zhang et al, 2023). Among legume-based proteins, several proteins (enzyme inhibitors, lectins, and storage globulins) and peptides (lunasin and hydrophobic peptides) extracted from legumes have shown significant health benefits such as anticancer, antiaging, hypoglycemic, antioxidant, antibacterial, and immune-stimulating properties ( Carbonaro & Nucara, 2022;Garcés-Rimón et al, 2022;Hu et al, 2023).…”
Section: Bioactive Protein and Peptidementioning
confidence: 99%
“…The protein extraction from peas, chickpeas, and other beans has attracted attention due to its good amino acid balance and high protein bioavailability (Zhang et al, 2023). Among legume-based proteins, several proteins (enzyme inhibitors, lectins, and storage globulins) and peptides (lunasin and hydrophobic peptides) extracted from legumes have shown significant health benefits such as anticancer, antiaging, hypoglycemic, antioxidant, antibacterial, and immune-stimulating properties ( Carbonaro & Nucara, 2022;Garcés-Rimón et al, 2022;Hu et al, 2023).…”
Section: Bioactive Protein and Peptidementioning
confidence: 99%
“…They have been shown to exhibit potent bioactivities, such as antiinflammatory function. 29 In a previous study, we observed that ER peptides tended to bind to lipopolysaccharide (LPS) in a physiologically relevant ion environment. 27 This binding capability may enable ER peptides to capture LPS in the GIT and ultimately ameliorate LPS-induced host inflammatory conditions.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Soybean peptides are derived through the digestion or hydrolysis of soybean proteins using various proteases. They have been shown to exhibit potent bioactivities, such as anti-inflammatory function . In a previous study, we observed that ER peptides tended to bind to lipopolysaccharide (LPS) in a physiologically relevant ion environment .…”
Section: Introductionmentioning
confidence: 99%
“…As a traditional legume crop, soybean (Glycine max) has been cultivated in China for nearly 5000 years, and China is the world's largest soybean processing and consumption country (X. Guo et al, 2021;S. Hu et al, 2023).…”
Section: Introductionmentioning
confidence: 99%